Does Organizational Culture Affect the Perception Towards the Barriers of the Glass Ceiling? - Muruatetu, Ndunge (2011)
Purpose : The purpose of this study was to examine the existence of the glass ceilling in Africa; and to investigate whether organizational culture affected the perception towards the barriers of the glass ceiling.